Communication competence of social workers in rehabilitation: interpersonal, empathic, and adaptive dimensions - Pusnita, Indah; Santoso, Budi; Aryani, Desi; Sjuchro, Dian Wardiana; Damin, Zahrul Akmal (Universitas Padjadjaran, 2026)
Background: Social workers require a high level of communication competence in providing social rehabilitation services. Communication competence involves the ability to communicate effectively, empathetically, and adaptively according to clients’ needs and social conditions. In social rehabilitation, these competencies are essential for building trust, facilitating participation, and supporting successful intervention outcomes. Social workers ability to establish rapport, communicate empathetically, and tailor communication strategies to clients’ situations may affect the success of social support and intervention. Yet, empirical studies, particularly in South Sumatra, remain limited. Therefore, examining social workers’ communication competence in Sentra Budi Perkasa, as one of leading social rehabilitation institutions in South Sumatra, is important to provide insights for improving service quality and strengthening professional social work practice. Purpose: This study aims to analyze the communication competence of social workers at Sentra Budi Perkasa, Palembang, South Sumatra, Indonesia. Methods: It employs a qualitative case study design. The data collection includes in-depth interviews with social workers, participant observation as social workers engage in the rehabilitation process, and a review of pertinent institutional records. Results: The interpersonal, empathic, and adaptive dimensions reflect the communication competence of social workers at Sentra Budi Perkasa Palembang. Openness, clear language, and active listening can help social workers gain clients’ trust. Conclusion: The study concludes that social workers’ communication competence is a strategy to optimize the quality of social rehabilitation services. Implications: It is believed that the research findings could provide a foundation for enhancing social workers’ abilities by continually training them in communication and practice, and guiding them to formulate humanistic, participatory, communication-based social rehabilitation service policies.